Implementasi Peraturan Walikota Kupang Nomor 90 Tahun 2020 Tentang Penerapan Penggunaan Protokol Kesehatan di Era Pandemi Covid-19 di Wilayah Kota Kupang - Aryana Ruthstine Heo; Saryono Yohanes; Hernimus Ratu Udju (International Forum of Researchers and Lecturers, 2023)
Policy Implementation is in principle a rare or way that is done so that the policy can achieve its goals. Policy implementation aims to measure the extent of the impact on society and the extent of implementation achieved. This type of research is empirical juridical research. The types and sources of data used are primary and secondary data. Primary data is data obtained directly from the research location through direct interviews with respondents and based on researcher observations. Secondary data is data obtained from literature studies. The data was analyzed descriptively qualitatively. Based on the results of this study, it shows that (1) The effectiveness of the policy implementation of the Kupang Mayor Regulation on the Use of Health Protocols, namely: (a) Kupang City government participation, (b) government performance. (2) Factors inhibiting the implementation of the law are: (a) Limited qualified human resources, (b) limited facilities and infrastructure, (c) the mindset of the community regarding the enforcement of health protocols.